MEDICAL HIGHER EDUCATION IN DEVELOPING UZBEKISTAN: PROBLEMS OF EDUCATION QUALITY AND REFORMS IN MEDICAL INDUSTRY - Sattorova, Dildora Gapparovna; Ahmadi, Behnaz (Educational Research in Universal Sciences, 2023)
In this article, the quality of the medical industry in regard to the recent decrees of the republic of Uzbekistan is being analyzed. Also, the effects of the reforms in the laws effecting the medical studies are being considered. As a result of the study, it is found that most of the established new laws are being neglected by the official and the signs of these neglection is visible in the treatment procedure of the population. Hence, we can say that the recent reforms in law will be unsuccessful unless it is applied effectively by the help of authorized organizations.